Effects of propylene glycol on the metabolic status and milk production of dairy buffaloes - Hussein, H. A.; Abdel-Raheem, S. M.; Abd-Allah, M.; Senosy, W. (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2015)
Objectives: The study was designed to investigate the effects of drenching with propylene glycol (PG) on body condition, serum metabolites and milk production during the transition period of dairy buffaloes. Material and methods: Animals were randomly allocated to a control group (n = 5) and a PG group of 10 buffaloes that were drenched with 500 ml of propylene glycol once daily from 10 (9 ± 3) days prepartum until 2 weeks postpartum. Ultrasound measurements of backfat thickness (BFT) were performed weekly, while blood samples were taken at –4, –2, 2, 4, 6, and 8 weeks from parturition for estimation of hematological and biochemical metabolites. Results: At –4, –3, and –2 weeks from calving, BFT did not differ between the two groups, but decreased after calving and was higher for the control group than the PG group at weeks –1 and 1. Hematological analysis revealed insignificant changes between the two groups. Serum concentrations of non-esterified fatty acids (NEFA), β-hydroxybutyric acid (BHBA) and glucose did not differ between the two groups before parturition. At 2 and 4 weeks from parturition, NEFA was higher for the control group than the PG group. Serum concentrations of BHBA were higher at 2, 4, 6, and 8 weeks in control animals than in treated buffaloes. In contrast, the glucose level was significantly increased in PG group when compared to the control group at week 2 postpartum (p < 0.05). Serum concentrations of total cholesterol, triglycerides, total proteins, albumin, and globulins did not differ significantly between the two groups (p > 0.05). Serum enzyme activities of aspartate aminotransferase and γ-glutamyl transferase were significantly higher in the control than in the PG group. In treated buffaloes significantly (p < 0.05) higher average 60-day milk yields were recorded (8.4 ± 0.22 vs. 10.7 ± 0.40 kg/day). Milk composition did not differ between the two groups. Conclusion and clinical relevance: Drenching of dairy buffaloes with propylene glycol may reduce the risk of ketosis, improve the metabolic status, and increase the milk yield.
Keywords: Buffaloes; propylene glycol; metabolic status; milk production; transition period